Pemberdayaan Remaja Guna Meningkatkan Minat Literasi Kesehatan Mental di Era Digital: Adolescent Empowering to Increase Mental Health Literacy Interest in the Digital Era - Khoiriyah Isni; Farikhah Nur Laila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
WHO data in 2017 shows that there are still high cases of depression in Indonesia among children, adolescents, and early adults. This is due to the limited knowledge of adolescents related to mental health literacy. This training aim is to increase adolescent expertise about mental health literacy to help adolescents. The methods used in this service activity include education, training, case studies, simulations, and role-playing. Activities are carried out in compliance with health protocols. The training activity involved 25 youth of the Warungboto Village, held for two days at the Pendopo Umbulharjo District, Yogyakarta. The results obtained from this dedication are differences in adolescents' knowledge before and after giving education about mental health literacy. Participants can analyze mental health problems and provide solutions to these problems. The importance of mental health literacy helps adolescents recognize the issues in themselves to seek help/assistance appropriately.